On Hollywood : the place, the industry - Scott, Allen John (Princeton University Press, 2005)
"Why is the U.S. motion picture industry concentrated in Hollywood and why does it remain there in the age of globalization? Allen Scott uses the tools of economic geography to explore these questions and to provide a number of highly original answers. The conceptual roots of his analysis go back to Alfred Marshall's theory of industrial districts and pick up on modern ideas about business clusters as sites of efficient and innovative production."